Virtual Support in Dementia: A Possible Viable Strategy for Caregivers - Ferretti, Ceres; Nitrini, Ricardo; Brucki, Sonia M. D. (Frontiers in Neurology, 2021)
Background: In the last 10 months, due to the Covid-19 pandemic, several studies have shown that health education and virtual support strategies for caregivers of patients with dementia, in the management of home care, can be viable. Low and middle income countries, in particular, have sought to use these means to reduce the daily burden of caregivers, through virtual meetings of education and support. Objectives: To present the feasibility of a pilot study on the use of a support action contemplated by the Caad Project–indirect costs of dementia–from HC-FMUSP. Methods: Observational study in which 93 caregivers were invited to participate in virtual meetings on a frequency of three times/week, lasting 1 h each. Results: Of the 93 invited family members, and after 3 months, 42 answered eight questions about the effectiveness of the action. High percentages of positive responses regarding program satisfaction ranged from 86 to 100%. Conclusion: This study showed results of a very simple intervention that suggests that it is possible to offer caregivers of patients with dementia a program that can be used in primary care, in order to understand the difficulty of caregivers in their daily care of patients with dementia, with daily management guidelines on a case-by-case basis, in addition to promoting the implementation of an education strategy about the importance of knowing, and recognizing anatomophysiological changes in the aging process and its implications for the rupture of the imaginary line that involves senescence and senility. This allows the caregiver to feel able to protect his patient and himself by preventing the emergence of common diseases in this age group. Further studies are needed to explore this type of non-pharmacological support.